Evaluation of the immunogenicity and efficacy of an rVSV vaccine against Zika virus infection in macaca nemestrina - Tisoncik-Go, Jennifer; Voss, Kathleen M.; Lewis, Thomas B.; Muruato, Antonio E.; Kuller, LaRene; Finn, Eric E.; Betancourt, Dillon; Wangari, Solomon; Ahrens, Joel; Iwayama, Naoto; Grant, Richard F.; Murnane, Robert D.; et al. (Frontiers in Virology, 2023)
Zika virus (ZIKV) is a mosquito-borne flavivirus that causes an acute febrile illness. ZIKV can be transmitted between sexual partners and from mother to fetus. Infection is strongly associated with neurologic complications in adults, including Guillain-Barré syndrome and myelitis, and congenital ZIKV infection can result in fetal injury and congenital Zika syndrome (CZS). Development of an effective vaccine is imperative to protect against ZIKV vertical transmission and CZS. Recombinant Vesicular Stomatitis virus (rVSV) is a highly effective and safe vector for the delivery of foreign immunogens for vaccine purposes. Here, we evaluate an rVSV vaccine expressing the full length pre-membrane (prM) and ZIKV envelope (E) proteins (VSV-ZprME), shown to be immunogenic in murine models of ZIKV infection, for its capacity to induce immune responses in nonhuman primates. Moreover, we assess the efficacy of the rVSVΔM-ZprME vaccine in the protection of pigtail macaques against ZIKV infection. Administration of the rVSVΔM-ZprME vaccine was safe, but it did not induce robust anti-ZIKV T-cell responses, IgM or IgG antibodies, or neutralizing antibodies in most animals. Post ZIKV challenge, animals that received the rVSVΔM control vaccine lacking ZIKV antigen had higher levels of plasma viremia compared to animals that received the rVSVΔM-ZprME vaccine. Anti-ZIKV neutralizing Ab titers were detected in a single animal that received the rVSVΔM-ZprME vaccine that was associated with reduced plasma viremia. The overall suboptimal ZIKV-specific cellular and humoral responses post-immunization indicates the rVSVΔM-ZprME vaccine did not elicit an immune response in this pilot study.